Does the Work Environment of F&B Service Department Change During and After the Covid-19 Pandemic? A case study at the Fairfield By Marriott Bali Legian Hotel - Margresye Diana Rompas; Deisy Ch. Andih; Geertruida E. Lalamentik; Fonny Sangari; Alma K. Pongtuluran; Frans V. Rattu; Benny Irwan Towoliu (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
This study aims to examine the conditions and changes in the work environment at the Food and Beverage (F&B) Department of Fairfield by Marriott Bali Legian Hotel during and after the Covid-19 pandemic, with particular attention to shifts in Standard Operating Procedures (SOPs). The recovery of the tourism sector has become increasingly visible following the significant decline in Covid-19 cases, rising vaccination coverage, relaxed travel policies, and the emergence of “revenge tourism,” which collectively boosted tourist mobility. Using a qualitative descriptive research method, data were collected through observations, interviews, and documentation, and then analysed using data reduction, data presentation, and conclusion drawing. The findings indicate that substantial changes occurred across multiple dimensions of the work environment, including the physical environment (such as physical distancing arrangements, table spacing, and sanitation facilities), the social environment (team interactions, division of tasks, and communication flow), and the organisational environment (adjustments to SOPs, workflow modifications, and workload management). These dimensions experienced the most significant transformation during the pandemic as the department adapted to health protocols and operational constraints. Following the pandemic, however, the F&B Service Department has largely returned to its pre-pandemic norms, although some organisational adaptations particularly those related to hygiene standards continue to be maintained as part of improved operational practices